Senam Lansia terhadap Tekanan Darah pada Lansia dengan Hipertensi - Lina Safarina; Neng Fuji; Andria Pragholapati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of elderly exercise on blood pressure in the elderly with hypertension. The method used is a pre-experimental design with one group pre-test and post-test. The results showed that the mean systolic blood pressure before the elderly exercise intervention was 160.00 mmHg, with a standard deviation of 8.083. While the mean value of systolic blood pressure after the elderly exercise intervention was 131.77 mmHg with a standard deviation of 4.799. On diastolic blood pressure, it was found that the mean value of diastolic blood pressure before the elderly exercise intervention was 88.92 mmHg with a standard deviation of 6.211. The results of diastolic blood pressure showed that the average value of diastolic blood pressure after the elderly exercise intervention was 82.31 mmHg with a standard deviation of 3.276. The analysis showed that systolic and diastolic blood pressure decreased with a systolic value = 0.001 and a diastolic value = 0.001. In conclusion, there is an effect of elderly exercise on blood pressure in older adults with hypertension after elderly activity in RW 16 and Posbindu Kenanga Work area of ​​Cipageran Health Center, both systolic and diastolic. Keywords: Hypertension, Elderly, Elderly Gymnastics